Current status and management of canine leishmaniasis in Latin America - Marcondes, Mary [UNESP]; Day, Michael J. (Elsevier, 2019)
Latin America encompasses diverse geographical, cultural and socio-economic conditions, which are reflected in the challenges for infectious disease control in the region. One of the most significant regional infectious diseases for humans and domestic dogs is leishmaniasis, occurring as visceral leishmaniasis (VL) caused by Leishmania infantum (syn. L. chagasi) transmitted by sand flies (Lutzomyia longipalpis) and with a canine reservoir, and the more common cutaneous leishmaniasis (CL) involving multiple Leishmania spp. (particularly L. braziliensis), sand fly vectors and reservoir hosts. VL is spreading within Latin America for reasons related to mass migration of human and canine populations, with incursion into novel environments (e.g. related to deforestation) coupled with a background of poverty and poor public health infrastructure. The challenges for control of VL also include: (1) the accurate identification of infected dogs (particularly subclinically infected dogs) with the current reliance on serological rather than molecular diagnostic methods, (2) controversy surrounding the ethics and efficacy of culling of seropositive dogs, (3) the limited efficacy of currently available canine vaccines and their potential to interfere with interpretation of serological testing, (4) the expense associated with distribution of insecticidal dog collars, which may prove to be the most valuable control method, and (5) the cost and therefore accessibility of licensed medical treatment for canine leishmaniasis by the general population. Resolution of these isssues will necessitate a ‘One Health’ approach to co-ordination of resources between human and veterinary healthcare.
Keywords: Cutaneous leishmaniasis; Dog; Epidemiology; Infectious disease control; Visceral leishmaniasis